Teknologi Tepat Guna Pompa Hidram untuk Kebutuhan Irigasi Perkebunan Pisang di Desa Kalikatir pada Musim Kemarau - Habib Fazad Amrullah Al-Fasih; M. Rizal Pratama; Keane Kenze Nekea; Jason Nathanael Marpaung; Jhos Franklin Kemit (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2026)
The R05 Community Service Program (KKN), Subgroup 1 in Kalikatir Village, Gondang District, Mojokerto Regency, aims to implement hydram pump technology as an environmentally friendly and energy-efficient irrigation solution. This technology is designed to meet the water needs of 100 hectares of banana plantations, especially during the dry season. The implementation method includes initial surveys, design, manufacture, installation, and testing of the hydram pump, involving the participation of Kalikatir villagers. The results show that the pump is capable of lifting water to a height of 30 meters with 70% efficiency, although it has not yet reached the daily target. This technology has been proven to reduce operational costs and increase agricultural productivity. It is hoped that in the future, this technology can be further developed to improve its efficiency and sustainability.